Sampah Bernilai: Edukasi Literasi Sampah Dan Kerajinan Sampah Untuk Lingkungan Berkelanjutan - Adisti Nur Aisyah; Agus Riyanto; Evana Sanyya; Candra Reza Kurniawan; Sintia Yohana Aksah; Nabilatul Maulisa; Rizky Pratama; Inten Maya Lestari; Tisna Fatkhatun Khasanah; Estri Utaminingsih; Mamluatul Hikmah; Kharisma Ibnu Rasyid; Jayanti Nofiana Nur (CV. Multi Kreasi Media, 2024)
The project